Purification of zebrafish erythrocytes as a means of identifying a novel regulator of haematopoiesis - Kulkeaw, Kasem (Br J Haematol, 2017)
Zebrafish embryos are useful to study haematopoietic gene function in vertebrates, although lack of antibodies to zebrafish proteins has limited the purification of specific cell populations. Here, we purified primitive zebrafish erythrocytes using 1, 5-bis{[2-(di-methylamino)ethyl]amino}-4, 8-dihydroxyanthracene-9, 10-dione (DRAQ5™), a DNA-staining fluorescent dye. At 48-h post-fertilization, we sorted small-sized cells from embryos using forward scatter and found that they consisted of DRAQ5(high) and DRAQ5(low) populations. DRAQ5(high) cells contained haemoglobin, lacked myeloperoxidase activity and expressed high levels of embryonic globin (hbae3 and hbbe1.1) mRNA, all characteristics of primitive erythrocytes. Following DRAQ5™ analysis of gata1:dsRed transgenic embryos, we purified primitive DRAQ5(high) dsRed+ erythrocytes from haematopoietic progenitor cells. Using this method, we identified docking protein 2 (Dok2) as functioning in differentiation of primitive erythrocytes. We conclude that DRAQ5™-based flow cytometry enables purification of primitive zebrafish erythrocytes.